Advances in Crowdfunding Research and Practice - Shneor, Rotem; Zhao, Liang; Flåten, Bjørn-Tore (Springer Nature, 2020)
This open access book presents a comprehensive and up-to-date collection of knowledge on the state of crowdfunding research and practice. It considers crowdfunding models and their different manifestations across a variety of geographies and sectors, and explores the perspectives of fundraisers, backers, platforms, and regulators. Gathering insights from a wide range of influential researchers in the field, the book balances concepts, theory, and case studies. Going beyond previous research on crowdfunding, the contributors also investigate issues of community, sustainability, education, and ethics. A vital resource for anyone researching crowdfunding, this book offers readers a deep understanding of the characteristics, business models, user-relations, and behavioural patterns of crowdfunding.